Stopover duration and field site selection by whooper swan (Cygnus cygnus) at Lake Tysslingen, Sweden - Hämäläinen, Louise (SLU/Dept. of Ecology, 2010)
The aim of this study was to increase the knowledge about whooper swan (Cygnus cygnus) ecology to enhance the ability to predict and also to prevent the crop damage they cause. The largest proportion of damage in Sweden has been reported at stopover sites during spring migration in February, March and April. Therefore, this study focused on an important stopover site, Lake Tysslingen, situated in south-central Sweden. Specifically, the relation between the duration and period migrating swans stage at the stopover site and mean temperature (measured at three different weather stations) for the years 2001-2010 was studied. Furthermore, the swans´ selection for certain fields in relation to field type, distance to roosting site, a supplemental feeding site and forest edge within agricultural land surrounding the lake was analyzed. I found a negative correlation between mean temperature in February (two last weeks) and the start of stopover period, i.e. a high mean temperature gives an early stopover start. Moreover, the duration of the stopover period depends on when the period starts, i.e. an early stopover start gives a long stopover period. During the study period the duration of the stopover period varied between 17 and 43 days. A supplemental feeding site used to attract swans within the area seem to be an efficient management tool since approximately 94% of the whooper swans stayed at this site and in the lake nearby during the stopover period. The remaining part (6%) was found on agricultural land and stubble fields were the most selected field type. Field site selection within the study area was not affected by the distance to roosting site, the supplemental feeding site or forest edge. Since stubble fields have already been harvested swans do not cause damage on these fields. The variation in temperature affects stopover duration and thereby also the risk of damage becomes difficult to predict between years.